Semiotics Analysis of Racism in the Comic Captain America: Sam Wilson - Junior, Maldini Radjab; Juanda (Tradition and Modernity of Humanity, 2022)
Racism is still common, especially against African Americans in the United States and is a problem that until now has not been resolved. Racism is again a hot topic as police brutality started popular movements such as Black Lives Matter that tried to raise awareness about racism in the United States. The comic "Captain America: Sam Wilson" describes the phenomenon of racism against society, especially in the United States. This article aims to find out the signs that represent racism in the comic "Captain America: Sam Wilson", signs that show verbal and non-verbal violence. This study uses a qualitative method with the semiotic approach of Roland Barthes. The data is taken from panels or scenes in the comic "Captain America: Sam Wilson," which contains racism. From the data obtained.